(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Economic growth is the increase in per capita availability of goods and services. Production of goods and services requires many inputs or resources from nature or the ecosystem: amines, water, air, solar energy, trees, animals, minerals, fossil fuels, metals, etc. In addition, many wastes—in solid, liquid, and air forms—are generated in the process of producing goods and services. All these waste materials are released into the environment